A critique of Mark Colvin's, crime and coercion: an integrated theory of chronic criminality - Daktari Alexander, A. (Crime, law and social change, 2002)
Colvin (2000) argues that thepropensity for chronic criminal behaviorresults from developmental andsocialization processes that ultimatelyoriginate in the application of erraticcoercive control. He further argues thatthis process operates at multiple levels(i.e., individual, group, andorganizational). In addition, he arguesthat the relationship between the types ofcontrol and criminal behavior is mediatedthrough intergenerational and developmentaleffects, suggesting that the control typethat has the greatest effect on behavior isone that will be passed on to the nextindividual, group, or organization.In this paper, we critique the theoryproposed by Colvin. First, we summarizethe theory. Second, we categorize it interms of its relationship to other types ofcriminology theories. Third, we criticizeit for failing to sufficiently specify itsempirical assertions in order to facilitateempirical testing, and we suggest sixhypotheses that we think capture at least asmall portion of the theory itself.